2016
DOI: 10.1016/j.amjsurg.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Role confusion and self-assessment in interprofessional trauma teams

Abstract: Background Trauma care requires coordinating an interprofessional team, with formative feedback on teamwork skills. We hypothesized nurses and surgeons have different perceptions regarding roles during resuscitation; that nurses’ teamwork self-assessment differs from experts’, and that video debriefing might improve accuracy of self-assessment. Methods Trauma nurses and surgeons were surveyed regarding resuscitation responsibilities. Subsequently, nurses joined interprofessional teams in simulated trauma res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Sargeant and colleagues suggest that there are four phases of self‐assessment: 1) receiving feedback from external sources, 2) reflecting on feedback to reconcile with self‐assessment, 3) plan to use feedback, and 4) use feedback for improvement and learning. Often during simulation training feedback from instructors can be important, and researchers have suggested that debriefing is beneficial . Students can perceive peer and faculty debriefing as equally effective .…”
Section: Discussionmentioning
confidence: 99%
“…Sargeant and colleagues suggest that there are four phases of self‐assessment: 1) receiving feedback from external sources, 2) reflecting on feedback to reconcile with self‐assessment, 3) plan to use feedback, and 4) use feedback for improvement and learning. Often during simulation training feedback from instructors can be important, and researchers have suggested that debriefing is beneficial . Students can perceive peer and faculty debriefing as equally effective .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the IS literature, patient safety researchers have long investigated issues of ownership, notably in patient handoffs when the care team changes, 19 interprofessional role misunderstandings in various settings, 20 , 21 and issues related to “chain-of-command.” 22 Our data demonstrate that the deployment of UTS for Lynch Syndrome can be viewed as a series of handoffs along a clinical pathway. Lessons from patient safety research show that paying attention to why and when a task is done, and what prompts help to ensure task completion, can inform successful handoffs.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of one's specific role and responsibilities is critical to an effective response. 36,37 In this study, significant gaps were reported in relation to participants' knowledge of core MCE response activities. Approximately one-quarter of participants had no or minimal knowledge of the phases of a major emergency response, with one-fifth having no or minimal knowledge of what their role would be in the case of an MCE.…”
Section: Knowledge Of Core Major Emergency Clinical Response Activitiesmentioning
confidence: 77%